The use of quality tools in the development of the singular psychomotor therapeutic project for children with autism: A systematic review (Research, Society and Development, 2025)
In a global scenario in which Autism Spectrum Disorder (ASD) is a clinical and social imperative that requires new strategies for therapeutic interventions for children, psychomotricity stands out as an important ally in promoting motor development and improving communication and social interaction. However, studies show the lack of deterministic tools in the development of the Singular Therapeutic Project (PTS) during treatments. Considering the knowledge in quality engineering and the use of its tools in the healthcare field, with emphasis on the PDCA cycle, Failure Mode and Effect Analysis (FMEA), the GUT Matrix and 5w1h, this study aims to investigate the intersection between quality tools, psychomotricity and autism, through a systematic literature review. The scopus and pubmed databases were used to search for articles using the keywords “autism”, “quality tools”, “psychomotricity”, among other variants. The results reveal low indicators of publications on the subject, mainly in Brazil, revealing a pioneering field for future application research within this subject.